1987
DOI: 10.3109/00365528709089768
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Secretory Response to Intestinal Stimulants: A Review

Abstract: Singer MV. Pancreatic secretory response to intestinal stimulants. Scand J Gastroenterol 1987, 22(suppl 139), 1-13In humans and many laboratory animals, protein digestion products such a s peptides and amino acids and fat digestion products such as fatty acids and monoglycerides are potent intestinal stimulants of pancreatic cnzymc secretion. The pancreatic enzyme response to these intestinal stimulants is related to thc pcrfuscd load (amount per unit time) rather than to concentration. Both neural and hormona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 68 publications
1
31
0
Order By: Relevance
“…In normal condi- tions, both neural (entero-pancreatic, cholinergic, vagovagal reflexes) and hormonal (cholecystokinin) pathways mediate the pancreatic enzyme response to intestinal stimulants. CCK seems to be the major mediator of the response to high loads of amino acids and fatty acids (19). Immuno-histochemistry identified approximately 1650 CCK cells per cross-section in the duodenum of humans (20) and jejunal mucosal integrity is necessary for the normal secretion of enteric hormones by the respective cells located in the small bowel mucosa (10).…”
Section: Discussionmentioning
confidence: 99%
“…In normal condi- tions, both neural (entero-pancreatic, cholinergic, vagovagal reflexes) and hormonal (cholecystokinin) pathways mediate the pancreatic enzyme response to intestinal stimulants. CCK seems to be the major mediator of the response to high loads of amino acids and fatty acids (19). Immuno-histochemistry identified approximately 1650 CCK cells per cross-section in the duodenum of humans (20) and jejunal mucosal integrity is necessary for the normal secretion of enteric hormones by the respective cells located in the small bowel mucosa (10).…”
Section: Discussionmentioning
confidence: 99%
“…In sea bass, pancreatic lipase activity increased with dietary triglyceride level ranging from 13% to 23%, showing a threshold, around 20% triglycerides, at which the maximum lipase activity and messenger RNA level were reached (Cahu et al, 2003). However, it has been suggested that the intestinal receptors for intraluminal stimulants require only a very low concentration for activation, meaning that the length of the intestine exposed to these products is the main determinant of pancreatic secretory response (Singer, 1987). If fish larvae showed similar response, the ingestion rate of the diet might also play a major role in determining lipase activity.…”
Section: Tablementioning
confidence: 99%
“…The effect of section of the vagus nerves on the response of the pancreas to secretin has produced conflicting results, from an unchanged response or a reduced response to no response at all (for references see Grundy, Hutson & Scratcherd, 1983). The contribution of the vagus nerves to the control of pancreatic secretion varies from species to species (for references see Harada, Nakagawa &Kato, 1982 andSinger, 1987). In an attempt to differentiate between vagal and hormonal control, both pharmacological and nerve section have been used.…”
Section: Introductionmentioning
confidence: 99%